Pemanfaatan Media Online INSTAGRAM Untuk Meningkatkan Kualitas Literasi Mahasiswa KPI A UINSU Semester 6 - Andika Fadli Nasution; Arif Syafi’i; Fatih Ichtisam; Nabillah Miftahul Jannah; Nurdini Lady Taminta Br Purba; Vania Daffa Yusriyah Daulay (Lembaga Pengembangan Kinerja Dosen, 2024)
Literacy quality is an important aspect in developing students' abilities, especially in the current digital era. This research aims to explore the use of the online media Instagram in improving the literacy quality of students of the Islamic Communication and Broadcasting Study Program (KPI) A, North Sumatra State Islamic University (UINSU) in semester 6. The research method used is qualitative with a case study approach. Data was collected through in-depth interviews and observations of participants who actively use Instagram in their academic activities. Research findings show that creative and targeted use of Instagram can improve the literacy quality of KPI A UINSU students. Through the available visual and text features, students can expand their knowledge about current issues in the field of Islamic communication and broadcasting, as well as improve their reading, writing and critical thinking skills. Apart from that, collaboration between students and lecturers via Instagram also opens up space for in-depth discussion and reflection, increasing understanding and appreciation of lecture material. The implication of this research is the importance of integrating social media in learning strategies to facilitate the holistic development of student literacy in higher education.